2016
DOI: 10.1055/s-0035-1565141
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning Enhances Muscle Endurance during Sustained Isometric Exercise

Abstract: Ischemic preconditioning (IPC) enhances whole-body exercise endurance. However, it is poorly understood whether the beneficial effects originate from systemic (e. g., cardiovascular system) or peripheral (e. g., skeletal muscle) adaptations. The present study examined the effects of IPC on local muscle endurance during fatiguing isometric exercise. 12 male subjects performed sustained isometric unilateral knee-extension exercise at 20% of maximal voluntary contraction until failure. Prior to the exercise, subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(126 citation statements)
references
References 28 publications
(51 reference statements)
10
115
1
Order By: Relevance
“…Beaven et al (2012) compared the early (immediate) and late (24 h later) effects of IPC on power production, and they found that IPC showed beneficial effects in both periods 8) . In addition, a recent study investigated the effects of IPC on static leg extension exercise and found that the endurance time to task failure was significantly longer in IPC than in CON 26) . Compared to its performance in whole-body exercise, it is possible that IPC may be more effective in improving exercise performance during local muscle contraction.…”
Section: Sprint (Cycle) Performancementioning
confidence: 99%
See 4 more Smart Citations
“…Beaven et al (2012) compared the early (immediate) and late (24 h later) effects of IPC on power production, and they found that IPC showed beneficial effects in both periods 8) . In addition, a recent study investigated the effects of IPC on static leg extension exercise and found that the endurance time to task failure was significantly longer in IPC than in CON 26) . Compared to its performance in whole-body exercise, it is possible that IPC may be more effective in improving exercise performance during local muscle contraction.…”
Section: Sprint (Cycle) Performancementioning
confidence: 99%
“…Because the peak values of blood lactate concentration (LApeak) after exercise may be an indicator of anaerobic capacity, several studies compared the LApeak between IPC and the control (or SHAM), and no effect in LApeak after exercise with IPC was found 4,[9][10][11][12][13][14]18,19,22) . Two studies focused on muscle activity, assessed by electromyography (EMG), between IPC and CON, and no differences in EMG were found during cycle sprints 4) or isometric leg extension 26) .…”
Section: Physiological Responses At Maximal Work Loadmentioning
confidence: 99%
See 3 more Smart Citations